(untitled) (Orfeu, 2017)
From research conducted in recent years, I realized that despite the large number of studies devoted to the subject, free improvisation keeps today, a very broad and imprecise definition. In fact, there are currently in Brazil and in the world, many artistic practices that include procedures that refer explicitly or not, to free improvisation. So one of the challenges that arises is, on the one hand, the search for a definition of what would be common (especially in terms of sound materials and procedures) between multiple and diverse practices that are located in the vast territory of free improvisation or which make use of it and, second, what would be unique and specific to each of these practices. First of all, it is necessary to establish whether there is actually a common territory that covers all these practices to further segment it into sub categories with their own identities. And more than that, it is necessary to unravel the building of consistency building processes in each case. In this paper I intend to make a preliminary survey in view of the above outlined goals. I’m also interested in discussing to what extent and how these various manifestations interact with certain social, cultural and political contemporary settings or, in other words, determine the extent to which free improvisation can be considered both as a symptom and as a line of force that contributes specifically to the setting of certain contemporary socio-cultural contexts related to creative practices.